English Teacher Interest in Utilizing English Apps in Teaching - Hasanah, Imroatul (Proceeding International Conference on Education, 2023)
Artificial intelligence-based English apps, both web-based and mobile-based, have recently been massive. They offer users huge benefits especially for non-native students to enhance their English skills. Such applications should assist Indonesian students since English is a foreign language. This research aims to find out how interested English teachers are in utilizing apps in teaching and what factors influence it. This qualitative research is carried out with a semi-structured interview method that involves 9 English teachers from 7 schools spread across some areas in East Java Province. Embracing junior and senior high school levels is because English is a compulsory subject based on the current curriculum in Indonesia, Kurikulum Merdeka. Using thematic content analysis, the research reveals that only one English teacher employs English apps for supporting the teaching and learning of English while the remaining ones preserve traditional ways and media. The low interest in applying the English apps is because of some factors: 1) inadequate facilities like school computers and Wi-Fi, 2) no mobile phone for students in some schools, especially Islamic boarding schools, and 3) lack of teacher knowledge about certain good English apps. Hopefully, this research contributes to better knowledge and awareness about the importance of utilizing artificial intelligence such as English apps in teaching English to gain better education in the sophisticated era.